Analisis Risiko Keselamatan dan Kesehatan Kerja Pada Pemeliharaan dan Perawatan Sistem Utilitas Bangunan Gedung Icon Mall Gresik - Gatot Basuki HM (Universitas Katolik Parahyangan, 2021)
Maintenance of the Icon Mall Gresik building is carried out in order to provide convenience for consumers when shopping, traders and building tenants. Every maintenance and maintenance activity has a risk of work accidents that may occur for workers. The research objective is to determine risk assessment and risk identification and determine the status of system failure and its determination. After analyzing the existing risks and system failures that can occur, then making suggestions for improvements with mitigation actions that are expected to reduce the rate of work accidents. The results showed that there were five groups of building utility maintenance jobs with 116 job risks. The results of risk measurement showed that 7 jobs were categorized as high risk. Meanwhile, risk mitigation is divided into 4 levels which result in improvement proposals, namely using Personal Protective Equipment (PPE) Safety Harness, repairs by managers and periodic building maintenance to avoid utility disruptions, providing boundary lines on engine room holes and carrying out work in accordance with standards. structured operational procedures by the management of the Icon Mall Gresik Building, especially for workers in the engineering department.